Estudo da variação do meio na produção de metabólitos secundários pelo fungo endofítico Aspergillus niger - Araujo, Nailson Correia de (2010)
The endophytic fungus Aspergillus niger isolated from specie plant Hancornia speciosa, commonly known as mangabeira, was cultivated in different culture media and used for identification of six substances in their extracts, such as oxalic, citric, tartaric, p-acetylbenzoic, hexylitaconic acids and phyrofen. For quantification of pyrophen in different extracts, it was developed a method by High Performance Liquid Chromatography that was efficient for both extract analysis and fermented broth. The method allowed to evaluate the effect of different media ways and culture time on the pyrophen. The analyzed media for pyrophen production were mangaba juice, Czapeck and potato dextrose broth (PDB) and the highest yield was obtained using mangaba juice. The effect of culture time was evaluated by cultivating the fungus in the PDB medium, being the ideal period of fermentation for pyrophen production was 12 days.